\[\boxed{\text{720\ (720).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ \left( m^{2} - 2m \right)^{2} - 1 =\]
\[= (m^{2} - 2m - 1)(m^{2} - 2m + 1)\]
\[2)\ 16 - \left( m^{2} + 4m \right)^{2} =\]
\[= (4 - m^{2} - 4m)(4 + m^{2} + 4m)\]
\[3)\ x² - 18xy + 81y^{2} - z^{2} =\]
\[= (x - 9y)^{2} - z^{2} =\]
\[= (x - 9y + z)(x - 9y - z)\]
\[4)\ 64x² + 48xy + 9y² - 144 =\]
\[= (8x + 3y)^{2} - 144 =\]
\[= (8x + 3y - 12)(8x + 3y + 12)\]
\[5)\ c² - a^{2} + 22a - 121 =\]
\[= c^{2} - (a - 11)^{2} =\]
\[= (c - a + 11)(c + a - 11)\]
\[6)\ 100 - 25y^{2} - 60x^{2}y - 36x^{4} =\]
\[= 100 - \left( 5y + 6x^{2} \right)^{2} =\]
\[= (10 - 5y - 6x^{2})(10 + 5y + 6x^{2})\]
\[\boxed{\text{720.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1){\ (a + b)}^{2} + (a - b)^{2} =\]
\[= 2 \cdot (a^{2} + b^{2})\]
\[Преобразуем\ левую\ часть\ \]
\[равенства:\]
\[a^{2} + 2ab + b^{2} + a^{2} - 2ab + b^{2} =\]
\[= 2a^{2} + 2b^{2} = 2 \cdot \left( a^{2} + b^{2} \right)\]
\[2a^{2} + 2b^{2} = 2 \cdot (a^{2} + b^{2})\]
\[2 \cdot \left( a^{2} + b^{2} \right) = 2 \cdot \left( a^{2} + b^{2} \right).\]
\[Тождество\ доказано.\]
\[2)\ (a + b)^{2} - (a - b)^{2} = 4ab\]
\[Преобразуем\ левую\ часть\ \]
\[равенства:\]
\[a^{2} + 2ab + b^{2} - a^{2} + 2ab - b^{2} =\]
\[= 4ab\]
\[2ab + 2ab = 4ab\]
\[4ab = 4ab.\]
\[Тождество\ доказано.\]
\[3)\ a^{2} + b^{2} = (a + b)^{2} - 2ab\]
\[Преобразуем\ правую\ часть\ \]
\[равенства:\]
\[a^{2} + b^{2} = a^{2} + 2ab + b^{2} - 2ab\]
\[a^{2} + b^{2} = a^{2} + b^{2}.\]
\[Тождество\ доказано.\]
\[4)\ \left( a^{2} + b^{2} \right)\left( c^{2} + d^{2} \right) =\]
\[= (ac + bd)^{2} + (ad - bc)^{2}\]
\[Преобразуем\ обе\ части\ \]
\[равенства:\]
\[a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2} =\]
\[a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2} =\]
\[= a^{2}c^{2} + b^{2}d^{2} + a^{2}d^{2} + b^{2}c^{2}\]
\[a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2} =\]
\[= a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2}.\]
\[Тождество\ доказано.\]